Porosity and permeability relationships of the Lekhwair and Lower Kharaib Formations - Cox, Peter A. (The University of Edinburgh, 2011)
Up to 60% of the World’s oil is now within carbonates, with over 50% in the Middle East. Many existing carbonate fields have very low oil recoveries due to multiple scales of pore heterogeneity. To secure better recoveries the controls from deposition and diagenesis towards the origin of carbonate pore heterogeneity needs better understanding. To provide good sample support, three High frequency Cycle’s were sampled (2 from the Lekhwair Formation and the third being the Lower Kharaib Formation) from an offshore field (Abu Dhabi) along a southwest-northeast transect, encompassing the oil leg, transition zone, water leg, the field crest and two opposing flanks. With respect to deposition, the 4th order Sequence Boundaries’ (hardgrounds) and the Maximum Flooding Surface’s were correlated across the field, within the sequence stratigraphic framework, showing that each HFC, of the Lekhwair Formation, contains laterally continuous reservoirs (4th order HST’s) which are compartmentalised above and below by impermeable seals (4th order TST’s). The Lower Kharaib Formation shows significant shoaling producing the shallowest platform (prolonged 3rd order TST) and the best connected reservoir facies. With respect to diagenesis, δ 18O isotopes trends, from calcite cement zones within macrocements from the water and oil legs, in comparison with oil inclusion abundances suggest that oil charge reduced cementation in the crest macropores. Stylolitisation in the water leg at deep burial provided solutes for new cement nucleation causing near complete macropore occlusion. The most open micropore networks coincide with the highest porosity/permeability relationships at the mid-late HST’s of each HFC. Considering these areas could be lower grade reservoirs, and that pore characterisation by Lucia (1999) does not include identifying and quantifying micropores, a new ‘Micropore model’ (using elements from the Petrotype atlas method) is devised. This new method highlights micropore-dominated areas alongside macropore-dominated areas within specific reservoir horizons. This provides information of pore heterogeneity at several scales within a carbonate reservoir and may determine the method for oil extraction and increase oil recovery from both the Lekhwair and Lower Kharaib Formations.
The porosity and permeability relationships of the Lekhwair and Lower Kharaib Formations
Keywords: carbonate fields; carbonate pore heterogeneity; High frequency Cycle; HFCs; HSH's; pore heterogeneity; oil recovery